2009
DOI: 10.1007/s11552-009-9171-1
|View full text |Cite
|
Sign up to set email alerts
|

Transtrapezial Peritrapezoidal Transcapital Axial Radial Fracture Dislocation of the Carpus

Abstract: We report a unique pattern of an axial radial fracture dislocation of the carpus. The fracture dislocation line runs transtrapezial peritrapezoidal transcapital transmetacarpal III/IV. Open reduction and internal fixation was performed 11 days after the accident. The result at 9 months is moderate, with a range of motion of 63% and strength of 46% compared to the opposite side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(11 reference statements)
0
4
0
1
Order By: Relevance
“…They do argue that it is essential to conduct precise clinical and radiographic examinations for accurate and efficient treatment. 9 In our case, the decision to delay surgery for 11 days in the setting of extensive soft tissue swelling may have avoided wound complications and resulted in a satisfactory outcome at 6 months. The case reports of axial ulnar dislocations with associated perilunate injuries did not address soft tissue management or delay to definitive treatment.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…They do argue that it is essential to conduct precise clinical and radiographic examinations for accurate and efficient treatment. 9 In our case, the decision to delay surgery for 11 days in the setting of extensive soft tissue swelling may have avoided wound complications and resulted in a satisfactory outcome at 6 months. The case reports of axial ulnar dislocations with associated perilunate injuries did not address soft tissue management or delay to definitive treatment.…”
Section: Discussionmentioning
confidence: 66%
“…Another important aspect that warrants discussion is the soft tissue management in these patients. Hacki et al 9 reported a case in which there was a delay of 11 days before surgical intervention and suggested that the time-lapse has no negative impact. The outcome is highly correlated to the amount of soft tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…The classification of these injuries is distinct from that of perilunate injuries and is further complicated by the high association of axial carpal injuries with other bone and soft-tissue derangements (5). Since the 1989 review of 56 patients, 15 additional cases of axial carpal injury have been reported in the literature (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Classificationmentioning
confidence: 99%
“…This is believed to be due to the protective effect of the thenar soft tissues (5). These injuries can be isolated insults, can occur in association with perilunate or lunate dislocations (8,9,20), or can coincide with other complex carpal abnormalities (10)(11)(12)(13)(14)16,21).…”
mentioning
confidence: 99%
“…Verletzungen des Os trapezoideum werden als Folge schwerer Distorsions-, Stauchungs-und Quetschtraumata beobachtet [2]. Aufgrund der anatomischen Beschaffenheit des Os trapezoideum [11,12] und der Tatsache, dass das palmare Bandgefüge deutlich stärker ausgeprägt ist als der dorsale Bandapparat [12][13][14], kommt es häufiger zur dorsalen als zur palmaren oder radialen Luxation im STT-Gelenk [15]. Die Diagnosestellung dieser seltenen karpalen Verletzungen stellt eine große Herausforderung für die erstbehandelnden Ärzte dar.…”
Section: Introductionunclassified